FEATURES AND IMPORTANCE OF ACROBATIC EXERCISES - Hamroqulov Rasul; Mamajonova Zulfiyakhon (Journals Park Publishing, 2022)
Acrobatic exercise reduces the risk of many health conditions, ranging from heart disease to dementia. Although all forms of physical activity provide some benefits, acrobatic exercise is particularly effective because it causes the heart and lungs to work harder than usual.
Keywords: gymnastics, trainer, physics, sport, decision, experiment